Alcator C-Mod: research in support of ITER and steps beyond. (30th July 2015) - Marmar, E.S.; Baek, S.G.; Barnard, H.; Bonoli, P.; Brunner, D.; Candy, J.; Canik, J.; Churchill, R.M.; Cziegler, I.; Dekow, G.; Delgado-Aparicio, L.; Diallo, A.; et al.
Abstract: This paper presents an overview of recent highlights from research on Alcator C-Mod. Significant progress has been made across all research areas over the last two years, with particular emphasis on divertor physics and power handling, plasma–material interaction studies, edge localized mode-suppressed pedestal dynamics, core transport and turbulence, and RF heating and current drive utilizing ion cyclotron and lower hybrid tools. Specific results of particular relevance to ITER include: inner wall SOL transport studies that have led, together with results from other experiments, to the change of the detailed shape of the inner wall in ITER; runaway electron studies showing that the critical electric field required for runaway generation is much higher than predicted from collisional theory; core tungsten impurity transport studies reveal that tungsten accumulation is naturally avoided in typical C-Mod conditions.